Compressive/tensile deformation behavior and the correlated microstructure evolution of Ti–6Al–4V titanium alloy at warm temperatures - M. Paghandeh; A. Zarei-Hanzaki; H.R. Abedi; Y. Vahidshad; J. Kawałko; D. Dietrich; T. lampke (Journal of Materials Research and Technology, 2021)
The present study deals with the warm temperature deformation behavior of the Ti–6Al–4V alloy throughout investigating the flow behavior and the correlated microstructure evolutions. Toward this end, the tension and compression tests were conducted at temperatures of 100, 300, 500, and 600 °C under the strain rate of 0.001s−1. The low compressive formability of the material and premature fracture at 100 and 300 °C was attributed to the insufﬁcient number of operative slip systems at this relatively low temperature regime. In contrast, in tensile mode the work hardening capacity was increased and the portion uniform elongation was considerable. In fact, the higher activity of pyramidal slip systems and higher dislocation maneuverability in tensile mode provided a proper condition for substructure development, which resulted in higher strain accommodation. Interestingly, the tensile deformed microstructures at 100 and 300 °C were strongly texturized and most of α-grains were oriented around the midline of [0001]-[-1100] or even toward the [-1100]. This was attributed to the lower critical resolved shear stress of pyramidal slip in tension mode, which caused the rotation of the <c> axis toward extension direction. The significant flow softening in compressive mode and appreciable post-necking deformation (due to diffused necking) in tensile mode were the main characteristics of the flow curves at 500, and 600 °C. This was attributed to the extended dynamic recovery and continuous recrystallization, spheroidization, and geometric softening. It was believed that the intensified substructure development facilitated the fragmentation and boundary splitting mechanism, therefore, trigger the spheroidization of α phase.